2019
DOI: 10.1186/s12909-019-1650-7
|View full text |Cite
|
Sign up to set email alerts
|

Junior doctors’ early career choices do not predict career destination in neurology: 40 years of surveys of UK medical graduates

Abstract: Background The rapidly rising rates of brain diseases due to the growing ageing population and the explosion in treatment options for many neurological conditions increase the demand for neurologists. We report trends in doctors’ career choices for neurology; investigate factors driving their choices; and compare doctors’ original choices with their specialty destinations. Methods A multi-cohort, multi-purpose nation-wide study using both online and postal questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…While there have been: i) studies exploring which specialties junior doctors or medical students intend on pursuing (13,14,15,16,17,18), ii) studies which focused on career intentions of those pursuing one specialty or exploring factors that attract them to one speci c specialty (19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35), iii) studies speci cally focused on reasons why doctors are leaving the UK (36, 37,38,39,40), iv) studies exploring how medical students and junior doctors feel about speci c aspects of working within the NHS (41,42,43,44), v) studies investigating the desire for a career break post-foundation year 2 (also known as the 'F3') (45,46,47), there have been no recent, high-powered studies explicitly aimed at medical students, irrespective of current career ambitions or seniority, investigating overall career intentions and correlating it with demographic factors and medical student seniority. There has been one similar study, although focusing entirely on medical students and their intentions to leave the NHS, which is limited by its low power and lack of subanalysis regarding student seniority and demographic factor (48).…”
Section: Discussionmentioning
confidence: 99%
“…While there have been: i) studies exploring which specialties junior doctors or medical students intend on pursuing (13,14,15,16,17,18), ii) studies which focused on career intentions of those pursuing one specialty or exploring factors that attract them to one speci c specialty (19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35), iii) studies speci cally focused on reasons why doctors are leaving the UK (36, 37,38,39,40), iv) studies exploring how medical students and junior doctors feel about speci c aspects of working within the NHS (41,42,43,44), v) studies investigating the desire for a career break post-foundation year 2 (also known as the 'F3') (45,46,47), there have been no recent, high-powered studies explicitly aimed at medical students, irrespective of current career ambitions or seniority, investigating overall career intentions and correlating it with demographic factors and medical student seniority. There has been one similar study, although focusing entirely on medical students and their intentions to leave the NHS, which is limited by its low power and lack of subanalysis regarding student seniority and demographic factor (48).…”
Section: Discussionmentioning
confidence: 99%
“…While there have been: i) studies exploring which specialties junior doctors or medical students intend on pursuing (13, 14, 15, 16, 17, 18), ii) studies which focused on career intentions of those pursuing one specialty or exploring factors that attract them to one specific specialty (19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35), iii) studies specifically focused on reasons why doctors are leaving the UK (36, 37, 38, 39, 40), iv) studies exploring how medical students and junior doctors feel about specific aspects of working within the NHS (41, 42, 43, 44), v) studies investigating the desire for a career break post-foundation year 2 (also known as the ‘F3’) (45, 46, 47), there have been no recent, high-powered studies explicitly aimed at medical students, irrespective of current career ambitions or seniority, investigating overall career intentions and correlating it with demographic factors and medical student seniority. There has been one similar study, although focusing entirely on medical students and their intentions to leave the NHS, which is limited by its low power and lack of subanalysis regarding student seniority and demographic factor (48).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the many studies done on the choice of specialization among medical students. Several studies have shown that for most medical students their preference for specialisation changes during medical school and often also in the period after graduation [34][35][36][37] and that females seem to make the final decision later than males [38]. A survey of German medical graduates shows that 77% of students make the decision about their choice of specialisation in the final year of medical school [39].…”
Section: Discussionmentioning
confidence: 99%